The legal-canonical status of the national shrine of Our Lady of Lourdes - Adamczyk, Jerzy; Mazur, Karolina (Prawo Kanoniczne, 2025)
The study is an attempt to introduce the legal-canonical status of the national shrine of Our Lady of Lourdes in light of its statute. The article seeks to show the identity and peculiarity of the said shrine, which is formed by a “special cause of devotion” - Marian apparitions to St. Bernadette in the grotto at Lourdes - because of which crowds of the faithful make pilgrimages there every year. It goes on to outline the mission of the shrine, the persons and bodies responsible for the operation of this pilgrimage center, and the relationship of the shrine to ecclesiastical authority: the local diocesan bishop and the Episcopal Conference of France.